Analisis Kesulitan Guru dan Orang Tua Siswa dalam Implementasi Belajar dari Rumah (BDR) di Daerah 3t (Terdepan, Tepencil dan Terluar) Pada Muatan Pelajaran Bahasa Indonesia Aspek Keterampilan Membaca di Sekolah Dasar - desi sarwendah; Abdul Muktadir; Endang Widi Winarni (Universitas Bengkulu, 2022)
AbstractThe purpose of this study was to determine the difficulties of teachers in preparing learning implementation plans and the difficulties of parents in guiding students in the learning process from home in the aspect of reading skills. The researcher used a qualitative descriptive method. In this study, the data collection methods used were observation and interviews. The results showed that the fourth grade teacher at SDN Napalicin had difficulties in designing learning implementation plans and in assessing student work. The obstacle experienced by the teacher is when designing learning objectives. This is because teachers find it difficult to analyze student needs and student conditions when learning from home. The results of interviews with people on learning from home parents have difficulty in accompanying students while studying. The difficulty experienced is when there are assignments or materials that students do not understand and ask parents, parents do not understand the orders or assignments given. Efforts made by parents vary, some use the internet to find information, some ask neighbors or ask directly with teachers whose houses are close by. Considering that the pandemic situation is still ongoing, it is not possible to conduct face-to-face learning. In this case, it takes the creativity of a teacher in designing lesson plans in order to achieve learning objectives and improve student learning outcomes.